Evidence of high genetic connectivity for the longnose spurdog Squalus blainville in the Mediterranean Sea - KOUSTENI, V.; KASAPIDIS, P.; KOTOULAS, G.; MEGALOFONOU, P. (Mediterranean Marine Science, 2015)
Squalus blainville is one of the least studied Mediterranean shark species. Despite being intensively fished in several locations, biological knowledge is limited and no genetic structure information is available. This is the first study to examine the genetic structure of S. blainville in the Mediterranean Sea. Considering the high dispersal potential inferred for other squalid sharks, the hypothesis of panmixia was tested based on a 585 bp fragment of the mitochondrial DNA cytochrome c oxidase subunit I gene from 107 individuals and six nuclear microsatellite loci from 577 individuals. Samples were collected across the Ionian, Aegean and Libyan Seas and off the Balearic Islands. Twenty three additional sequences of Mediterranean and South African origin were retrieved from GenBank and included in the mitochondrial DNA analysis. The overall haplotype diversity was high, in contrast to the low nucleotide diversity. Low and non-significant pairwise ΦST and FST values along with a Bayesian cluster analysis suggested high connectivity with subsequent genetic homogeneity among the populations studied, and thus a high dispersal potential for S. blainville similar to other squalids. The historical demography of the species was also assessed, revealing a pattern of population expansion since the middle Pleistocene. These findings could be considered in species-specific conservation plans, although sampling over a larger spatial scale and more genetic markers are required to fully elucidate the genetic structure and dispersal potential of S. blainville.